Effect of heat and thermosonication treatments on peroxidise inactivation kinetics in watercress (nasturtium officinale) - Cruz, Rui M. S. (2010)
The effect of heat and the combined heat/ultrasound (thermosonication) treatment on the inactivation kinetics of peroxidase in watercress (Nasturtium officinale) was studied in the temperature range of 40-92.5 degrees C. In the heat blanching processes, the enzyme kinetics showed a first-order biphasic inactivation model. The activation energies and the rates of the reaction at a reference temperature for both the heat-labile and heat-resistant fractions were, respectively, E-a1 = 421 +/- 115 kJmol(-1) and E-a2 = 352 +/- 81 kJmol(-1), k(184.6 degrees C) = 18 +/- 14min(-1) and k(284.6 degrees C) = 0.24 +/- 0.14min(-1). The initial relative specific activity for both isoenzyme fractions were also estimated, being C-01 = 0.5 +/- 0.08 mu mol min(-1)mg protein(-1) and C-02 = 0.5 +/- 0.06 mu mol min(-1)mg protein(-1), respectively. The application of thermosonication was studied to enable less severe thermal treatments and, therefore, improving the quality of the blanched product. In this treatment the enzyme kinetics showed a first-order model. The activation energy, the rate of reaction at a reference temperature and the initial relative specific activity were, respectively, E-a3 = 496 +/- 65 kJmol(-1), k(387.5 degrees C) = 10 +/- 2min(-1) and C-03 = 1 +/- 0.05 mu mol min(-1)mg protein(-1), proving that the enzyme became more heat labile. The present findings will help to design the blanching conditions for the production of a new and healthy frozen product, watercress (Nasturtium officinale), with minimized colour or flavour changes along its shelf life.